Konkurencyjność operacyjna i strategiczna współczesnego przedsiębiorstwa - organizacji procesowej - Adamkiewicz-Drwiłło, Hanna (Strategic and Operating Competitiveness of Contemporary Business - Process Organization, 2009)
Problems of contemporary management are mainly connected with necessity of adaptation for fast changing market conditions. It seems very important to emphasize taking accurate and adequate to such conditions decisions. There are two kinds of decisions: current decisions - resolve upon operating business competitiveness and strategic ones - anticipate surroundings changes - condition efficient activity of the business in the future, improving its strategic competitiveness. The main goal of the article is to pay attention to existing of mentioned dependences assuming that a business is a process organization. Maximization of a client's satisfaction is one of the basic activities goals formulated for the business - process organization. Reaching the goal is possible if the business knowingly influences its own operating competitiveness, framed in a short period and strategic one - in a long period. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 357-365